Echocardiographic Evaluation of Poor R wave Progression in ECG (KYAMC Journal, 2026)
Background: Poor R wave progression on electrocardiography has long been associated with anterior myocardial infarction. However, in contemporary practice, its structural and functional correlates are inconsistent, and the true echocardiographic implications remain incompletely characterized.Objectives: To determine the prevalence of echocardiographic abnormalities among patients with poor R-wave progression and to assess their associations with socio-demographic factors, cardiovascular risk factors, comorbidities, and clinical symptoms.Materials and Methods: This hospital-based cross-sectional study included 196 adults with poor R-wave progression on standard 12-lead electrocardiography. All participants underwent transthoracic echocardiography to evaluate regional wall motion abnormalities, left ventricular hypertrophy, prior myocardial infarction patterns, and left ventricular ejection fraction. Categorical variables were summarized as frequencies and percentages. Associations between clinical variables and echocardiographic findings were assessed using Pearson’s chi-square test. Multivariable binary logistic regression was performed to identify independent predictors of regional wall motion abnormalities. A two-sided p-value